2019
DOI: 10.4236/apd.2019.83005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Utility of the Personal KinetiGraph<sup>®</sup> in the Management of Parkinson Disease

Abstract: INTRODUCTION: Parkinson's disease (PD) is a disorder characterized by complex motor and non-motor symptoms that can be difficult for patients to accurately communicate. Wearable technologies portend improvements in assessment and monitoring of these symptoms, with their clinical utility currently being evaluated in routine clinical care. OBJECTIVE: To evaluate the clinical utility of the Personal KinetiGraph® (PKG®) Movement Recording System in the routine clinical care of persons with PD (PWP). METHODS: Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…However, this metric could prove to be a useful baseline in determining the medication response time of individual patients. Several recent studies have shown that motor symptom data from wearable devices can help clinicians to better assess motor symptoms as well as to potentially alter medication schedule for better treatment and management of the disease ( 4 , 15 17 ). Patients wearing a PKG or other similar wearable sensor could provide their motor symptom data to clinicians, who would be able to use sensor data in conjunction with this response time finding to determine the magnitude of the response to medication as well as the individual's expected response time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this metric could prove to be a useful baseline in determining the medication response time of individual patients. Several recent studies have shown that motor symptom data from wearable devices can help clinicians to better assess motor symptoms as well as to potentially alter medication schedule for better treatment and management of the disease ( 4 , 15 17 ). Patients wearing a PKG or other similar wearable sensor could provide their motor symptom data to clinicians, who would be able to use sensor data in conjunction with this response time finding to determine the magnitude of the response to medication as well as the individual's expected response time.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinsonian patients may experience difficulty in recognizing and reporting their symptoms, and subjective recordings, such as surveys and diaries, can be prone to bias and inaccuracies (3). Thus, wearable sensors can provide objective symptom data that can help clinicians modify medications to more effectively manage symptoms of Parkinson's disease (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of the patient cohort and selection process are described in the study by Nahab et al 16 , which explored the clinical utility of the PKG in routine care of Parkinson's patients. All patients were selected from the UCSD Movement Disorder Center from June 2016 to March 2017.…”
Section: Study Cohortmentioning
confidence: 99%
“…All patients were selected from the UCSD Movement Disorder Center from June 2016 to March 2017. The study's inclusion criteria included: an age range of 46-83, being on levodopa, and a H&Y range 1-3 16 . The participants underwent two clinical assessment visits.…”
Section: Study Cohortmentioning
confidence: 99%